(untitled) (Philological Studies, 2019)
The article under consideration is the continuation of the studies of phonostylistic measuring of the Slavic literary symbolism. The article had analyzed the peculiarities of phonic of symbolic poetic text on the materials of poetry of Slavic symbolism by the representatives of different Slavic literatures, including the analysis of semantic plane of Slavic symbolism by means of typology of phonetic means of stylistics. The model of the world is dominated by Slavic symbolist auditory impressions that are dominant. Phonic picture of the world is regarded as a fragment of the language picture of the world, marked by the phonetic means, including sound recording, onomatopoeia, assonances, alliteration, internal rhymes that reproduce the sound view of the surroundings in the Slavic literary symbolism.